Hubungan Pengetahuan dan Sikap dengan Kesiapsiagaan Menghadapi Risiko Gempa Bumi dan Tsunami pada Siswa SMA - Huriani, Emil; Sari, Yanti Puspita; Harningsih, Nurfa Rahim (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2021)
Earthquake and tsunami have high risk level in Padang State that predict earthquake 8.9 Richter of MentawaiMegatrust. Padang State Senior High School 2 located in Red Zone of earthquake and tsunami and also close withBanda Bakali River. There are still found some students whose have not expressed enough knowledge related toearthquake and tsunami preparedness and not ready if disaster occur. This study aims to determine therelationship of knowledge and attitude with preparedness to confront earthquake and tsunami risk on students atPadang State Senior High School 2. Research design used analytics descriptive with cross sectional studyapproach to 280 respondents. The instrument of research consisted of 4 parts of questionnaire, which aredemographics data, knowledge, attitude, and preparedness. Research analysis used a comparative test by usingsoftware computer. The results of this study showed that 55.4% had high knowledge, 53.2% good attitudes, and66.1% moderate preparedness. In this result found that significant relationship between knowledge andpreparedness (p = 0.001) and significant relationship between attitude and preparedness with significance value(p = 0.000). Recommended to school to improve learning which more applicable for health promotion especiallyon earthquake and tsunami disasters that has been integrated in curriculum subject and held disasters simulationsearlier especially for new students